I spy. A thing that flings, and other stories [videorecording (DVD)] - Kaminsky, Jef; Zellers, Cote; Jayne, Tara; Lee, Ellen; Creekmore, Cindy; Big Al (I spy., 2004)
Spyler and CeCe lead young viewers through search and find adventures set in an imaginary world. Each story challenges them to find creative way to solve their problems.